Synthesis and Characterization of Heterocyclic Compounds and Polymers with Studying the Biological activity for some of them - Dhefaf H. Badri (Journal of Global Pharma Technology, 2016)
This paper deals with the preparation of new monomers and polymers which including heterocyclic unit. The diacid chlorides compounds [1-3] were prepared from the reaction of glutaric acid, adipic acid, terephthalic acid with thionyl chloride. Succinic acid reacted with ethanol to produce compound [4]. Compound [4] reacted with hydrazine hydrate to obtain succinic hydrazide [5].Compound [5] reaction with CS2 and KOH in absolute ethanol to produce compound [6].The polymers [7-12] have been created by reacting diacid chlorides compounds [1-3] with compound[5] or [6] in dry pyridine with some drops of DMF. The topology of produced compounds has characterized through their spectral and analytical data as in FT-IR spectra, Thermal analysis [DSC, TGA] and Antibacterial activity investigated using dual bacteria kinds.Keywords: Succinic hydrazides, Oxadiazole, Heterocyclic polymers.